Bicultural Identity Integration of Transracial Adolescent Adoptees: Antecedents and Outcomes. (July 2014) - Manzi, Claudia; Ferrari, Laura; Rosnati, Rosa; Benet-Martinez, Veronica
A number of studies have focused on Bicultural Identity Integration (BII) to explore whether and how migrants and ethnic minorities, who experience multiple cultural belongings, perceive their two cultural backgrounds as compatible (vs. conflictual) and to study the impact of these differences on their psychosocial well-being. Nevertheless, there is a lack of research on BII among transracial adoptees, who also experience unique conditions of dual cultural belonging. Relying on a sample of 170 adopted adolescents born in Latin American countries and subsequently adopted in Italy (aged between 15 and 25) and both of their parents, the aim of the present study was twofold: to explore whether and the extent to which BII is related to adoptees' behavioral problems and to analyze the influence of specific family and social identity variables on BII. Multivariate analyses using the structural equation modeling indicated that adoptive filiation (i.e., belonging to the adoptive family) and parents' cultural socialization strategies are significant protective factors for national identity and ethnic identity, respectively, which in turn influences adoptees' behavioral problems, but this relation is mediated by differences in BII.